2006
DOI: 10.1097/00124784-200607000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the Gap Between Public and Private Healthcare

Abstract: This article describes the development, testing, and implementation of the OKAlert-ILI System, a bidirectional, dual-use influenza-like illness surveillance and messaging system, during the influenza seasons of 2003-2004 and 2004-2005 in the Oklahoma Physicians Resource/Research Network, a primary care practice-based research network. We describe how the Oklahoma Physicians Resource/Research Network connected 30 primary care providers to the Oklahoma State Department of Health and how surveillance results were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
1
2
1
Order By: Relevance
“…Studies have reported that clinician perception of the care they provide, as well as actual diagnosis and use of resources, is improved when surveillance data are available to them [18, 19, 28, 34, 36–38]. However, we did not find significant differences between intervention and control clinics with regard to the clinician behaviors we measured.…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…Studies have reported that clinician perception of the care they provide, as well as actual diagnosis and use of resources, is improved when surveillance data are available to them [18, 19, 28, 34, 36–38]. However, we did not find significant differences between intervention and control clinics with regard to the clinician behaviors we measured.…”
Section: Discussioncontrasting
confidence: 80%
“…We minimized the possibility of a false positive early signal by defining our real-time surveillance alert as a peak that contained a point exceeding the upper control limit followed by a point that did not return to the center line rather than using a single point for the alert. Based on this conservative definition, the timeliness of our early alert was similar to that seen in other studies [2628]. However, further study using a confirmatory test such as viral culture or polymerase chain reaction would be required to determine whether these earlier peaks in our population are false positives or represent the earliest circulation of influenza in the population.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Approximately 280 clinicians in 170 practices throughout the state of Oklahoma comprise the OKPRN. Network members have participated in research on a broad array of topics, such as patient–physician email communication [31], patient social support and advocacy [32,33], health information technology and exchanges [34,35,36,37,38], preventive/screening services [39,40,41], hypertension management [42,43], management of lab test results [44], and prescription refills [45].…”
Section: Methodsmentioning
confidence: 99%